Волинська обласна організація Національної спілки краєзнавців у 2014–2019 роках (До 30-річчя Волинської обласної організації Національної спілки краєзнавців України) - Бондаренко, Г.; Шваб, А. (Краєзнавство, 2019)
Публікація присвячена 30-річчю Волинської обласної організації Національної спілки краєзнавців України, яка заснована у 1989 році. Розповідається про створення і діяльність обласної організації. Про тих,хто бувїї членами, представлені окремі осередкиЛуцького, Володимир-Волинского, Камінь-Каширского, Ковельського, Любомльського і Маневицького районов. Краєзнавці брали активну участь у пошуковій і дослідницькій роботі, у популяризації краєзнавства і поширені краєзнавчої освіти, зокрема волинезнавства. Брали участь у виконанні програм: підготовки циклу публікацій «Реабілітовані історією», «Книги Скорботи», «Зводу пам'яток історії та культури Волинська область», «Інтелектуальна еліта Волині», у конференціях «Минуле і сучасне Волині та Полісся» тощо. This publication is dedicated to the 30th anniversary of the Volyn regional organization of the National Union of Local Lore of Ukraine which was founded in 1989. It tells about the creation and activities of the organization, about those who were its members represented individual cells of Lutsk, Vladimir-Volynsky, Kamen-Kashirsky, Kovelsky, Lyubomlsky and Manevichsky areas. Local history experts took part in local history research, disseminated local history education, created and filled with content the course of Volynology for pupils and students. Local historians worked in conjunction with museum, library, and archival workers, with researchers and scientists from higher educational institutions. Separate programs were carried out to create a series of publications “Rehabilitated by History”, “The Set of Monuments of History and Culture in the Volyn Region”, “The Intelligent Elite of Volyn”, “The History of Local Self-Government” and others. An important place is occupied by the program for the preparation of the history of settlements of the Volyn region. In this direction, many books have been prepared and published in all areas of the region, which cover issues of history, nature, economics, culture. Many are dedicated to individual settlements, including those that for various reasons have ceased to exist on the map of the region. An important place is occupied by the program for the preparation of the history of settlements of the Volyn region. In this direction, many books have been prepared and published in all areas of the region, which cover issues of history, nature, economics, culture. Many are dedicated to individual settlements, including those that for various reasons have ceased to exist on the map of the region. Much attention is paid to political history, wars, revolutions and other events that local historians represent in their work. Many important issues of local history and local history education are considered at the conferences «The Past and the Present of Volyn and Polesie». The article names those who were studied by local historians, creating a pantheon of glory of the region. Round tables and workshops that address specific issues and problems in districts and settlements are attracting attention. Lists of UNAPSCU members and a list of references since 2014 are presented. The article names those who were studied by local historians, creating the pantheon of glory of the region. Round tables and workshops that address specific issues and problems in districts and settlements are attracting attention. Lists of UNAPSCU members and a list of references since 2014 are presented. Basically, local history information was submitted over the past five years because it was partially presented in publications dedicated to the Volyn Union every five years of its activity.